Mitigating greenhouse gas emissions from beef cattle production in brazil through animal management - D’aurea, André Pastori; da Silva Cardoso, Abmael [UNESP]; Guimarães, Yuri Santa Rosa [UNESP]; Fernandes, Lauriston Bertelli; Ferreira, Luis Eduardo; Reis, Ricardo Andrade [UNESP] (MDPI, 2021)
Beef cattle production is an important agricultural activity in Brazil, which influences environmental and resource consumption. This study analyzed greenhouse gas (GHG) emission impacts from 17 farms, representing the Brazil’s productive system and determined possible improvements in the production chain. Methane, nitrous oxide, and carbon dioxide emissions were evaluated using the updated Intergovernmental Panel on Climate Change (IPCC) guidelines for national inventories. The GHG inventory included emissions from animals, feeds, and “cradle-to-farm-gate” operations for animal management. Regression analyses of carbon dioxide equivalent (CO2 eq) emissions and productive indices were performed to identify possible GHG emission hotspots. The results varied considerably among the farms. The GHG yield ranged from 8.63 to 50.88 CO2 eq kg carcass−1 . The productive indices of average daily gain (p < 0.0001), area productivity (p = 0.058), and slaughtering age (p < 0.0001) were positively correlated with GHG yield. However, no correlation was found with the stocking rate (p = 0.21). The production chain could be improved through accurate animal management strategies that reduce the slaughtering age and daily weight gain individually or per area using pasture management and strategic animal supplementation, which could subsequently reduce GHG emissions in beef cattle production.
Keywords: Beef production; GHG emissions; GHG inventories; Livestock; Sustainable intensification